Autonomy and Firefighting: Perceived Competence and Stress. Issue 12 (December 2016) - Chiang, Evelyn S.; Baley, John; Ponder, Joy; Padilla, Miguel A.
Abstract : Objective: In workplace settings, autonomy is implicated in employee motivation as well as supervisor autonomy support. As a profession of risk, firefighters may experience greater levels of stress. Methods: A self-determination paradigm was applied to the firefighter workplace. Of particular interest were perceived competence (to perform job duties) and the experience of stress. Firefighters' levels of autonomous and controlled regulation were surveyed, along with their perceptions of the autonomy support of their immediate supervisor. Results: Autonomous regulation was positively related to perceived competence, whereas controlled regulation was negatively related. Higher levels of controlled regulation were also connected with greater stress. In contrast, greater perceived autonomy support was associated with decreased stress. Conclusions: Both perceived competence and stress are related to firefighter motivation and autonomy support. Recommendations are offered to increase autonomy support by chief officers.